Autologous stem cell transplantation is safe in selected elderly multiple myeloma patients. (12th December 2019) - Antonioli, Elisabetta; Nozzoli, Chiara; Buda, Gabriele; Staderini, Michela; Boncompagni, Riccardo; Martini, Francesca; Petrini, Mario; Bosi, Alberto; Saccardi, Riccardo
Abstract: Objectives: ASCT is currently the "gold standard" first‐line treatment for multiple myeloma patients younger than 65 years old, and limited data on efficacy and safety in older patients are available. Methods: We retrospectively analyzed a cohort of 83 newly diagnosed multiple myeloma patients aged 65 or older. All patients were evaluated for fitness at diagnosis and after bortezomib‐based induction treatment. Results and conclusions: All patients collected an adequate PBSC graft, mainly after G‐CSF plus cyclophosphamide; a median of 6.47 × 10 6 /kg CD34 + cells was collected. The conditioning regimen consisted of melphalan 100, 140 and 200 mg/m 2 in 40, 15 and 28 patients, respectively. Median time to neutrophils' and platelets' recovery was 11 and 12 days, respectively. Adverse events of any grade were referred by 40% of patients. The overall response rate was 93%, CR/sCR were 39%. Median PFS was 35 months; median OS was not reached. In our study cohort, the achievement of at least VGPR after induction therapy and the obtainment of CR/sCR after ASCT are the only parameters that were associated with an improved PFS. ASCT is an effective and safe first‐line treatment approach, a careful patients selection reduce the toxicity of the procedure.